Identification of a chromosomal locus for expression of lipopolysaccharide epitopes in Haemophilus influenzae. - Weiser, J N (1989)
Lipopolysaccharide (LPS) is a major virulence determinant of Haemophilus influenzae. The organism is able to display an extensive repertoire of different LPS structures through the loss and acquisition of multiple oligosaccharide epitopes in various combinations. This marked heterogeneity of LPS molecules has complicated the analysis of the structure of LPS and its role in pathogenesis. A genomic library was screened for the ability to transform H. influenzae to express novel LPS epitopes defined by reactivity with oligosaccharide specific monoclonal antibodies. A chromosomal locus, lic-1, involved in expression of at least three different epitopes (recognized by monoclonal antibodies 4C4, 12D9, and 6A2), was identified on a 5.6-kilobase restriction endonuclease fragment. Transformation of H. influenzae with subclones from within lic-1 was used to generate a series of isogenic and phenotypic variants. All transformants displayed phase variation for their newly acquired epitopes. Altered binding specificities of LPS with monoclonal antibodies correlated with changes in sugar compositional analysis. The expression of two epitopes was eliminated by introduction of site-specific mutations in lic-1, confirming the role of lic-1 in oligosaccharide biosynthesis.